Neuroprotective Effect of Ramipril Is Mediated by AT2 in a Mouse MODEL of Paclitaxel-Induced Peripheral Neuropathy - Hichem Bouchenaki; Amandine Bernard; Flavien Bessaguet; Simon Frachet; Laurence Richard; Franck Sturtz; Laurent Magy; Sylvie Bourthoumieu; Claire Demiot; Aurore Danigo (MDPI AG, 2022)
Paclitaxel (PTX)-induced peripheral neuropathy (PIPN) induces numerous symptoms affecting patient quality of life, leading to decreased doses or even to cessation of anticancer therapy. Previous studies have reported that a widely used drug, ramipril, improves neuroprotection in several rodent models of peripheral neuropathy. The protective role of the angiotensin II type 2 receptor (AT2) in the central and peripheral nervous systems is well-established. Here, we evaluate the effects of ramipril in the prevention of PIPN and the involvement of AT2 in this effect. Paclitaxel was administered in wild type or AT2-deficient mice on alternate days for 8 days, at a cumulative dose of 8 mg/kg (2 mg/kg per injection). Ramipril, PD123319 (an AT2 antagonist), or a combination of both were administered one day before PTX administration, and daily for the next twenty days. PTX-administered mice developed mechanical allodynia and showed a loss of sensory nerve fibers. Ramipril prevented the functional and morphological alterations in PTX mice. The preventive effect of ramipril against tactile allodynia was completely absent in AT2-deficient mice and was counteracted by PD123319 administration in wild type mice. Our work highlights the potential of ramipril as a novel preventive treatment for PIPN, and points to the involvement of AT2 in the neuroprotective role of ramipril in PIPN.